Heparin versus enoxaparine for prevention of asymptomatic deep venous thrombosis after total knee arthroplasty - Hnoosh, Adnan H.; Wahab, Mahmood S.; Khadim, Malik (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Venous thromboembolic disease (VTED) is a well known complication that occur following total knee arthroplasty (T.K.A). One of the (VTED) forms is asymptomatic deep venous thrombosis with an incidence has been estimated to be up to ³ 20% in patients undergone primary T.K.A , despite routine treatment with heparin postoperatively.Objectives : is to assess the prevalence of post-operative asymptomatic D.V.T among patients receiving two different thromboprophylactic drugs after T.K.A.Patients and methods: 68 patients who had T.K.A were randomly divided for the purpose of post-operative thromboprophylaxis into two groups , group [ A ] (control group) consisted of 35 patients received heparin, and group [B] of 33 patients received low molecular weight heparin (L.M.W.H) (enoxaparin) subcutaneously. Both groups were given the drug for two weeks post-operatively, then aspirin untill the 6th week after surgery. Bilateral Duplex U/S performed preoperatively and postoperatively at 5-7 days. The third ultrasonography was performed on the third week after surgery on all patients. the evaluation of the result expressed as primary efficacy outcome which was the composite of D.V.T (either symptomatic or detected by Ultrasonography  if the patient was asymptomatic). Non-fatal pulmonary embolism or death from any cause at 42 days after surgery, were also evaluated with a confidence interval (C.I.)Results: The overall incidence of asymptomatic D.V.T was 2.94% (2 in 68 patients). Those two patient were in heparin group; (group [A]) which represent 11.4% that is highly significant, while no cases (0%) reported among enoxaparin group; Group [B].Conclusion: Enoxaparin significantly lowered the prevalence of deep vein thrombosis (D.V.T.) after T.K.A.